Handbook of toxicology of chemical warfare agents - Gupta, Ramesh C. 1949- (Elsevier/Academic Press, 2009)
Covers various aspects of deadly toxic chemicals used as weapons of mass destruction and employed in conflicts, warfare and terrorism. This book covers individual toxicants, target organ toxicity, major incidents, toxic effects in humans, animals and wildlife, biosensors, biomarkers, and on-site and laboratory analytical methods.- Resumé vydavatel
Keywords: bojové chemické látky; toxikologie; chemical warfare agents; toxicology; elektronické knihy; sborníky; příručky; electronic books; papers of several authors; handbooks and manuals